2021
DOI: 10.1002/jac5.1503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a pharmacist‐to‐dose direct oral anticoagulant protocol on medication errors at an academic medical center

Abstract: Background: Direct oral anticoagulants (DOACs) are considered high-risk medications and pose a serious threat to patients if mismanaged. Furthermore, medication error rates involving DOACs in the acute care setting range from 25% to 40%. To reduce medication error rates at our institution, we implemented a pharmacist-driven DOAC protocol that permitted pharmacists to independently order and monitor DOACs pursuant to a consult order.Objective: To determine the impact of a pharmacist-to-dose DOAC protocol on med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Multiple studies have demonstrated the ability of pharmacist‐run stewardship initiatives in both inpatient and outpatient settings to optimize appropriate prescribing and dosing of DOACs 14,33 . In one study, implementation of a pharmacist‐to‐dose DOAC protocol was associated with a 44% reduction in DOAC‐related medication errors in hospitalized patients 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated the ability of pharmacist‐run stewardship initiatives in both inpatient and outpatient settings to optimize appropriate prescribing and dosing of DOACs 14,33 . In one study, implementation of a pharmacist‐to‐dose DOAC protocol was associated with a 44% reduction in DOAC‐related medication errors in hospitalized patients 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists are well‐equipped to optimize guideline‐directed anticoagulant therapy by identifying and converting appropriate patients. Several studies have demonstrated a positive effect of pharmacist‐led anticoagulation stewardship in improving appropriate DOAC prescribing 12–14 . A recent article by Kish and colleagues described a warfarin to DOAC conversion initiative during the coronavirus disease 2019 (COVID‐19) pandemic in pharmacist‐led anticoagulation clinics utilizing a “DOAC conversion checklist.” 15 However, data describing the impact of pharmacist‐driven anticoagulation (AC) stewardship in the inpatient setting is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that participants' confidence in prescribing DOACs to patients were boosted if they collaoborated with clinical pharmacists. Studies have shown that involvement of pharmacists in the appropriate selection of DOACs doses decreased errors [21,22]. Additionaly, pharmacists were able to reduce DOACs errors through medications reviews conducted during the hospital stay, at the clinics and through medication reconciliation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike conventional anticoagulation management, which is often siloed and focused solely on drug management, anticoagulation stewardship provides a holistic approach that spans the continuum of care, is focused on continuous quality improvement, and addresses patient‐level, clinician level, and system‐level barriers and opportunities to improve patient care. To address the ongoing pervasiveness of inappropriate anticoagulant prescribing and management, a growing number of health care institutions across the United States and globally have successfully implemented anticoagulation stewardship initiatives and assessed their impact in both inpatient and outpatient clinical settings 19–21 …”
Section: Figurementioning
confidence: 99%
“…To address the ongoing pervasiveness of inappropriate anticoagulant prescribing and management, a growing number of health care institutions across the United States and globally have successfully implemented anticoagulation stewardship initiatives and assessed their impact in both inpatient and outpatient clinical settings. [19][20][21] Koolian et al 16…”
Section: Control and Prevention Has Issued Core Elements For Antibioticmentioning
confidence: 99%